Gender dynamics of a Parents Support Group - Govender, Kevashini (Department of Psychology, 2014)
Using a Parents Support Group run in Cape Town, South Africa, the study aims to illustrate how the psychodynamic model is inadequate in providing an understanding of the gender dynamics within this group. The study takes on an interpretive approach to explore this research problem and employs qualitative techniques, which were found to be most suitable. Data were collected through the use of field notes that documented the process of the Parents Support Group. This group consisted of ten females and one male participant, ranging from 34 to 45 years of age and who come from a lower socio-economic stratum. Furthermore, to elicit additional data and to capture the multi-layered experienees of participants, semi-structured interviews were conducted with five female and one male participant who were selected from the Parent Support Group. The field notes and the data acquired from the interviews were analyzed through the method of textual analysis, which elicited five key themes. It was found that although the psychoanalytic model was inadequate in explaining certain dynamics within the Parents Support Group, feminism and social constructionism models were able to highlight how gender was key in the dynamics at play within the group. This finding was vital in making recommendations about gender sensitivity and training concerning therapeutic interventions.